If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + -6n = f Reorder the terms: -6n + 4q = f Solving -6n + 4q = f Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4q' to each side of the equation. -6n + 4q + -4q = f + -4q Combine like terms: 4q + -4q = 0 -6n + 0 = f + -4q -6n = f + -4q Divide each side by '-6'. n = -0.1666666667f + 0.6666666667q Simplifying n = -0.1666666667f + 0.6666666667q
| 6(c-15)=-48 | | -5.9=y+9.3 | | -63x/7=-36 | | 1+3+-10+-16+22+4+-4+3+6+3= | | 3x^2+13=58 | | 3x-4.5=7.5 | | X+12=2x+36 | | 10(5)+20y=30 | | 3x+(-2x)+x+7=x+3 | | -x+2(-2)=3 | | x+1=3243865230948790572738437832654783265 | | 2x^2(x^5)= | | 5(x-12)=3x-5+22 | | 2x+3(-2)=8 | | -5y-y=12 | | x/2-10=1/3 | | h/9-12 | | -3=3y+18x | | 5x-41=3-6x | | g(-14)=x | | 39=-8t-3 | | 2x+2y+2-x+2= | | log(8)16=x+1 | | 1(x+2)=-19 | | 57-40x=-263 | | 36-7x=3(2x-10) | | 7(7+w)=6(8+w) | | 43=-18k+2k+5 | | 59-31x=-96 | | 10(4)+20y=30 | | T^2+8= | | 3x+10-x=1+x-10 |